2006
DOI: 10.1177/112067210601600215
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Factors Influencing Visual Outcome following Surgical Excision of Subfoveal Choroidal Neovascularization in Age-Related Macular Degeneration

Abstract: Surgical excision of CNV for ARMD was effective for completely classic CNV, and better postoperative visual acuity was achieved in cases of small CNV. Given the fact that photodynamic therapy (PDT) has only been used in Japan since 2004, future study should compare PDT and surgical excision in Japanese subjects for relative merits against surgical risk and postoperative complications, to define indications for PDT and surgical excision.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In contrast, other previous studies have reported finding stabilization of the AMD and improvement of the visual acuity of the patients, especially in the cases with classic CNV, although a selection bias could not be definitively ruled out. 13 , 14 , 15 Based on these previous reports and the findings in the current case, we decided that the surgical removal of the CNV should be used as the following indications were found for the patient: 1) the CNV was of the classic type, 2) no additional retinal damage would be caused by retinotomy as the CNV removal was performed via the macular hole, 3) the procedure would lead to less risk of RPE damage during the CNV removal except at the site of the CNV, and 4) there would be less risk of bleeding during the CNV removal after the anti-VEGF therapy. Furthermore, because the half-life of the anti-VEGF agent is known to be shortened after vitrectomy, 16 stabilization of the AMD by CNV removal would help to reduce the number of the anti-VEGF treatments required.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, other previous studies have reported finding stabilization of the AMD and improvement of the visual acuity of the patients, especially in the cases with classic CNV, although a selection bias could not be definitively ruled out. 13 , 14 , 15 Based on these previous reports and the findings in the current case, we decided that the surgical removal of the CNV should be used as the following indications were found for the patient: 1) the CNV was of the classic type, 2) no additional retinal damage would be caused by retinotomy as the CNV removal was performed via the macular hole, 3) the procedure would lead to less risk of RPE damage during the CNV removal except at the site of the CNV, and 4) there would be less risk of bleeding during the CNV removal after the anti-VEGF therapy. Furthermore, because the half-life of the anti-VEGF agent is known to be shortened after vitrectomy, 16 stabilization of the AMD by CNV removal would help to reduce the number of the anti-VEGF treatments required.…”
Section: Discussionmentioning
confidence: 99%
“…PVR pathogenesis is complex; however it is likely that, following trauma or retinal detachment, RPE cells migrate from their normal anatomic compartment, proliferate, dedifferentiate, undergo an epithelial to mesenchymal transformation (EMT), respond to many stimuli, and help create an intravitreal membrane (Al-Khairi et al, 2008; Asaria and Gregor, 2002; Campochiaro, 1997; Cardillo et al, 1997; Glaser et al, 1987; Kruger et al, 2002; Shimada et al, 2006). It is likely that the RPE cells produce membrane contraction that generates tractional force leading to retinal detachment (Hinton et al, 2002; Jin et al, 2000; Mukherjee and Guidry, 2007; Sakamoto et al, 1994).…”
Section: Introductionmentioning
confidence: 99%